Comparison of nitrergic signaling in circular and longitudinal smooth muscle of murine ileum. Issue 3 (7th August 2017) - Voussen, B.; Beck, K.; Mauro, N.; Keppler, J.; Friebe, A.
Abstract: Background: Gastrointestinal (GI) motility originates from coordinated movements of circular (CM) and longitudinal (LM) smooth muscle. How the two muscle layers react individually to nitrergic input and how they integrate nitrergic signaling is not thoroughly understood. Methods: We used immunohistochemistry to unveil expression of NO‐sensitive guanylyl cyclase (NO‐GC) in the ileum. For functional analyses, we measured tone of ileal CM and spontaneous contractions in both ileal muscle layers from mice lacking NO‐GC globally (GCKO) and specifically in smooth muscle cells (SMC‐GCKO). Key Results: In contrast to other parts of the GI tract, NO‐GC was not expressed in ckit‐positive cells in ileum. NO‐GC expression was intense in platelet‐derived growth factor receptor α‐positive cells and in yet unidentified cells of myenteric plexus and serosa. Both CM and LM developed spontaneous contractile activity; frequency and duration of their spontaneous contractions were identical. The amplitude of spontaneous contractions in CM was increased in the absence of NO‐GC. In ileum from control (ctrl) animals, inhibition of NO‐GC increased whereas NO‐GC stimulation decreased tissue tone. In contrast, contractile activity in LM was not different between ctrl and knockout strains. Here, NO led to suppression of spontaneous contractions of ctrl ileum whereas GCKO tissue was unaffected. To our surprise, NO suppressed spontaneous contractions in SMC‐GCKO ileum indicating participation of other cell type(s). Conclusions and Inferences: NO‐GC in SMC is involved in the regulation of tone and amplitude of spontaneous contractions in ileal CM. In LM, NO induces suppression of spontaneous contractions via NO‐GC in a non‐SMC type. Abstract : NO‐sensitive guanylyl cyclase influences the amplitude of spontaneous contractions in murine ileal circular smooth muscle.